PENGARUH CASH HOLDING, PROFITABILITAS, DAN LEVERAGE TERHADAP PERATAAN LABA (STUDI KASUS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2013–2017) - Stela Revinsia, Vionesy; Rahayu, Sri; Lestari, Tri Utami (Aksara Public, 2019)
This study was conducted to determine the effect simultaneously and partially variable cash holding, profitability, and leverage to income smoothing in mining companies listed on the Indonesia Stock Exchange in 2013-2017. The method in this research is quantitative research method with the type of this research is descriptive verification of causality. The hypothesis in this study was tested using descriptive statistical analysis and logistic regression analysis using SPSS 25.0 software. Sampling technique used in this study is a purposive sampling technique that obtained 6 research samples within a period of 5 years so that obtained 30 units of sample mining companies listed on the Indonesia Stock Exchange in 2013-2017.The results showed that cash holding, profitability, and leverage simultaneously have a significant affect on income smoothing. Partially, cash holding has a positive and significant effect on income smoothing, while profitability is proxied by return on assets (ROA) and leverage is proxied by a debt to asset ratio (DAR) does not have a significant effect on income smoothing.